2000
DOI: 10.1097/00000542-200012000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Muscle Relaxants during Radical Retropubic Prostatectomy

Abstract: The study hypothesis was confirmed. However, an isoflurane-fentanyl anesthetic alone produced a good to excellent surgical field in approximately two thirds of patients undergoing radical retropubic prostatectomy without the use of muscle relaxants. Thus, the routine use of muscle relaxants in adequately anesthetized patients undergoing this procedure may not be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 18 publications
0
44
0
2
Order By: Relevance
“…Many surgeons strongly advocate complete intraoperative muscle paralysis with little evidence that this practice essentially improves surgical conditions. 28 % of patients undergoing radical retro-pubic prostatectomy without neuromuscular blockade had unacceptable surgical conditions compared to 2 % of the patients who had received vecuronium [18]. Compared to lower abdominal surgery, we expected a higher demand for muscle paralysis in upper abdominal and even more in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many surgeons strongly advocate complete intraoperative muscle paralysis with little evidence that this practice essentially improves surgical conditions. 28 % of patients undergoing radical retro-pubic prostatectomy without neuromuscular blockade had unacceptable surgical conditions compared to 2 % of the patients who had received vecuronium [18]. Compared to lower abdominal surgery, we expected a higher demand for muscle paralysis in upper abdominal and even more in laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 93%
“…We decided to perform this study, because thorough literature search revealed only two studies investigating this daily discussed question, in one the surgeons were not blinded [22], in the other study blinding was questioned by the authors themselves [18]. Accordingly, the study design was tailored in favour of the hypothesis by two extreme regimes of muscle paralysis for laparoscopic surgery which is known to be very sensitive for inadequate muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Even traditional thinking, such as the reasoning that good diaphragmatic relaxation lowers intra-abdominal pressure, and hence is necessary for abdominal surgery, has been questioned. Whereas one recent human study showed that neuromuscular blockade could improve operating conditions in abdominal surgery, 69 another study in laparoscopic surgery did not show any influence of diaphragmatic relaxation on intra-abdominal pressure or inspiratory pressure. 70 Due to the complex interaction of several factors creating good operating conditions, such as depth of anesthesia, surgical exposure and skills, and the degree of muscle relaxation at the operating site, the influence of the degree of diaphragmatic relaxation on certain operating conditions is hard to judge.…”
Section: Importance Of Neuromuscular Block At the Diaphragmmentioning
confidence: 90%
“…9 Although clinical judgment of surgical conditions (e.g., adequate relaxation) can be subjective, recent studies have shown that NMBDs can improve surgical conditions, most specifically in abdominal surgery. 10,11 Neuromuscular blockade can be used to maintain a lighter plane of anesthesia; profound NMB can be useful for procedures such as intracranial surgery or complex eye surgery where even slight movement could result in critical events.…”
Section: Rationale For Routine Monitoring Of Neuromuscular Functionmentioning
confidence: 99%